Meta-Analisis Optimalisasi Kualitas Pembelajaran Matematika Dengan Integrasi STEM - Nendra Mursetya Somasih Dwipa (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2022)
Meta-analysis is a technique that uses certain measures to show the strength of the relationship between similar variables in a number of different research results. The unit of analysis in this study is the thesis reports of UPY mathematics education students taking the topic of integrating STEM (science, technology, engineering, mathematics) in learning mathematics. This study provides an introduction to the description of the implementation of STEM in students' mathematics learning, specifically aimed at knowing the improvement of the quality of the learning. The analytical technique used is library analysis on research reports taken purposively based on the research objectives. Quantitative analysis was carried out on percentage and nominal data, while qualitative analysis was carried out on study descriptions related to STEM implementation. The results of this study indicate that (1) in the aspect of mathematics learning outcomes, learning with STEM integration is able to describe students' abilities in the cognitive, affective, and psychomotor domains, (2) STEM learning is able to improve the quality of students' mathematics learning  Keywords: Meta-Analysis, STEM, Quality, Learning